Pandangan Islam tentang Mbesur-Mbesuri Bulanan pada Tradisi Adat Karo di Desa Belinteng Kecamatan Sei Bingai Kabupaten Langkat - Ikhsan, Alfatah (ANWARUL, 2023)
In Belinteng Village, Se Bingai District, Langkat Regency, the Mbesur-mbesur tradition is still often carried out by the Karo people. symbolized in the foods served by family members. the type of research used in writing this research is descriptive qualitative type. Descriptive qualitative is research where the researcher is placed as a key instrument, data collection techniques are carried out by combining and inductive data analysis. The results of this study indicate that Islamic law applies to the implementation of the mbesur-mbesuri tradition in Belinteng Village, Sei Bingai District, Langkat Regency. That in the mbesur-mbesuri tradition it can be done, what is important is that people do not believe in the symbols associated with the mbesur-mbesuri tradition. Mbesur-mbesuri is also a manifestation of gratitude to Allah SWT. So that with these mbesuri, the community does one manifestation of gratitude and prays and hopes for something good that will be obtained. In addition, it is a legacy from the ancestral culture. The hope that is expected in the mbesur-mbesuri procession is achieved by worship that has been determined in the Shari'a.